Fine‐needle aspiration findings of Xp11 translocation renal cell carcinoma metastatic to a hilar lymph node. Issue 5 (10th February 2017) - El Naili, Reima; Nicolas, Marlo; Gorena, Amanda; Policarpio‐Nicolas, Maria Luisa C.
Abstract : Xp11 translocation renal cell carcinoma (RCC) is a specific type of renal cell carcinoma recently placed under the "MiT family translocation RCC" at the last 2013 ISUP Vancouver classification of renal neoplasia. This tumor contains variable proportions of clear cells and could easily mimic papillary RCC, clear cell type, and clear cell papillary RCC. Given the small number of published cytologic findings of this tumor, it could easily present as a diagnostic pitfall. We describe a case of a 23‐year‐old man with a history of prior nephrectomy who presented with multiple mediastinal lymphadenopathies on imaging surveillance follow‐up. Fine‐needle aspiration of the lymph node showed tumor cells with voluminous clear to eosinophilic cytoplasm, well‐defined cell borders and hyperchromatic nuclei arranged in papillary architecture. Review of the prior nephrectomy specimen showed papillary cores surrounded by cells with voluminous clear to finely granular eosinophilic cytoplasm and distinct cell borders. Immunohistochemical stains performed on the nephrectomy specimen showed tumor positivity for CD10, E‐cadherin, a‐methylacyl coenzyme A racemase, and TFE3 supporting the diagnosis of Xp11 translocation renal cell carcinoma. Although this tumor was initially described predominantly in children, it could also occur in adults, as seen in this case. Familiarity with the cytologic findings of this tumor, use of immunohistochemical stains, or cytogenetic test to determine the type of gene fusion will be extremely useful in arriving at the correct diagnosis. Diagn. Cytopathol. 2017;45:456–462. © 2017 Wiley Periodicals, Inc.